Studies on Ramulus ussurianus (Bey-Bienko, 1960) (Phasmida: Phasmatidae) - Storozhenko, Sergey Yu.; Kim, Taewoo (Zootaxa, 2021)
The phasmid genus Ramulus Saussure, 1862 belongs to the nominotypical tribe of subfamily Clitumninae of the Phasmatidae. This genus consists of 159 species distributed in India (21 species), Sri Lanka (6 species), Bhutan (1 species), Myanmar (6 species), Thailand (1 species), Vietnam (12 species), Malaysia (4 species from Peninsular part and Borneo), Indonesia (18 species from Java, Sumatra, Borneo, Sulawesi, and Key islands), the Philippines (3 species), China including Taiwan (74 species), Japan (1 species), Korea (1 species), and Russia (1 species) (Brock et al., 2021). Three phasmid species have been described in the genus Baculum Saussure, 1861 from the Russian Far East, Korea and North-East China respectively (Bey-Bienko, 1960; Kwon et al., 1992; Chen & He, 1994) and later transferred to the genus Ramulus (Otte & Brock, 2005). As a result of detailed examination of the type specimens of Ramulus ussurianus (Bey-Bienko, 1960), additional material and descriptions of these species, it became clear that specimens from Russia, Korea and North-East China are conspecific.